A study on effectiveness of topical steroid therapy in boys with phimosis in the age group of 5 to 10 years - Kumar, S. Selva; Kumar, S. Santha; Shirley, S. Alph (International Journal of Contemporary Pediatrics, 2020)
Background: Phimosis defined as the inability to retract the prepuce over the glans of penis is a common condition affecting boys. Objective was to study the effectiveness of topical steroid therapy (0.05% clobetasol propionate cream) in boys with phimosis in the age group of 5 to 10 years. Methods: This retrospective observational study was conducted at the Department of Pediatrics and Department of Surgery at Arunai Medical College and Hospital, Thiruvannamalai, Tamilnadu, India among 74 boys in the age group of 5 to 10 years with phimosis. The effect of twice daily application of 0.05% clobetasol propionate cream for six weeks on phimosis was studied. Results: out of the 74 boys, 25 (33.78%) were in the age group of 5 to 6 years, 20 (27.02%) in the age group of 7 to 8 years and 29 (39.19%) in the age group of 9 to 10 years. As per Kikiros et al system of grading of retraction of foreskin, majority of the boys 30 (40.54%) were grade 4, followed by grade 2 (24 boys, 32.43%), grade 3 (14 boys, 18.93%) and grade 5 (6 boys, 8.1%). Out of the 74 boys with phimosis, 53 boys (71.62%) had associated complications. After 6 weeks of topical steroid therapy, 39 (52.71%) boys showed complete response, 24 (32.43%) boys showed partial response and 11 (14.86%) boys showed no response to the treatment regimen. There was no significant correlation between age of boys and grade of phimosis with treatment response. Significant correlation was noted between history of urinary tract infection and treatment response. None of the other complications showed significant correlation with treatment response. None of the boys had any side effects to topical steroid therapy. Conclusions: Topical steroid application can be tried as an effective treatment modality in boys with phimosis in the age group of 5 to 10 years.